Futuro con esperanza: Juventud, conocimiento y liderazgo - González Sáenz, Manuel (2015)
Speech the Foreign Minister Manuel A.Gonzalez, on the occasion of the inaugurallecture of the first cycle 2015 of the School ofInternational Relations at the National University,on February 17, 2015.